Ewolucja budżetowania przejawem dynamiki rozwoju współczesnych przedsiębiorstw - Bielawski, Rafał (Budgeting and its evolution towards flexibility as a sign of development of contemporary enterprise, 2005)
The contents of the article refers the conception of budgeting as a basic method of enterprise's management. This article shows the types of budgets and the ways of building them. The last part of the article refers to the new trends of management. This trends negates classical budgeting tries to replay it by new more elastic methods and techniques of management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 201-207